Modified Magnetic Nanoparticle-Based Solid-Phase Extraction for the Determination of Trace Amounts of Aflatoxins B1 and B2 in Chinese Patent Medicines: The Use of Fupuganmao Granules as a Case Study. (23rd November 2019) - Li, Qing; Jiang, Luyi; Zhang, Huan; Wei, Mengmeng; Chu, Chu; Yan, Jizhong
Abstract: Background: Aflatoxins (AFs) have attracted increasing amounts of attention in recent years for their high toxicity. Previously, AF-polluted Chinese Patent Medicines (CPMs) were ignored, but their quality, safety, and efficacy might be influenced by the toxic compounds. Objective: The objective is to develop a simple, low-cost, and efficient method for quantitative analysis of aflatoxins B1 (AFB1 ) and B2 (AFB2 ) in CPMs to ensure their safe use. Methods: A simple, modified, magnetic nanoparticle-based solid-phase extraction (SPE) combined with HPLC-fluorescence detection for the determination of trace amounts of AFB1 and AFB2 was established. The main parameters affecting the efficiency of modified magnetic nanoparticle-based SPE, such as pH of sample solution, adsorbent amount, adsorption time, and desorption condition, were investigated. Results: Under the optimum conditions, AFB1 and AFB2 were linear in the ranges of 0.3–10 and 0.04–3 ng/mL with the correlation coefficient ( R ) of 0.9998 and 0.9999, respectively. Their intraday precisions were 1.16 and 2.30% and the interday precisions were 1.28 and 1.87% for AFB1 and AFB2, respectively. The developed SPE was applied for AFB1 and AFB2 extraction in three commercially available Fupuganmao granule samples, and the results were compared with the official immunoaffinity column chromatography method. Conclusions: The method provided a preferable candidate for the determination approach of AF measurement in CPMs. Highlights: Amine-functionalized magnetic nanoparticles were successfully applied to SPE for adsorbing AFB1 and AFB2 in CPMs for the first time.